The association between team‐level social capital and individual‐level work engagement: Differences between subtypes of social capital and the impact of intra‐team agreement. Issue 2 (19th February 2018) - Meng, Annette; Clausen, Thomas; Borg, Vilhelm
Abstract : The study explored the association between team‐level social capital and individual‐level work engagement. Questionnaire data were collected from six companies in the dairy industry. Seven hundred seventy‐two participants divided into 65 teams were included. In confirmatory factor analyses, we found a superior model fit to a four dimensional model of social capital: bonding social capital, bridging social capital and two types of linking social capital. The results showed a positive association between all subtypes of social capital at the team level and work engagement at the individual level. However, this association only remained significant for linking social capital in relation the workplace as a whole when we adjusted for psychosocial working conditions. The level of intra‐team agreement in social capital score did not moderate the association between social capital and work engagement. In conclusion, the results provide further support for previous findings suggesting a positive association between social capital and work engagement. They add to the existing knowledge by suggesting that linking social capital in relation to the workplace is the most important explanatory variable for work engagement, thus emphasizing the need to distinguish between subtypes of social capital in research and practice.